311 Exploring the relationship between community sports participation and diabetes risk factors in youth - Leesi George-Komi; Frank Dolecki; Eric Hoe; Eric An; Leah E. Robinson (Journal of Clinical and Translational Science)
Objectives/Goals: Youth-onset diabetes and its risk factors are increasing in ethnic and racial minority communities. Our mixed-methods study aimed to explore the associations between participation in a community youth sports program and key diabetes risk factors in youth, including mental health, physical activity, nutrition, and weight status. Methods/Study Population: We used a single cohort, mixed-methods design focused on the Community Leadership Revolution (CLR) Academy, a local youth sports program. Participants, ethnic and racial minority youth ages 5–14, were recruited to assess their mental health, physical activity, and nutrition using validated and reliable questionnaires. Weight status was measured via bioelectrical impedance. Group interviews with youth and individual interviews with staff provided context for the quantitative results. A thematic analysis of the qualitative data will further explore how CLR Academy may impact diabetes risk factors. Results/Anticipated Results: We recruited 24 CLR participants (16 boys/8 girls) and 4 CLR staff (3 males/1 female). Sixteen youth identified as African-American, while the rest identified as multiracial. Correlations revealed that higher attendance at CLR Academy was negatively associated with mental health scores, specifically total, externalizing, and hyperactive scores (all p < 0.01). Higher CLR attendance was negatively associated with physical activity during spare time (p < 0.05), waist circumference (p< 0.05), and waist-to-height ratio (p < 0.01). Being a girl was associated with lower diet quality and physical activity (both p < 0.05). Qualitative data highlighted life skills and supportive relationships in CLR as key factors in improving health outcomes. Thematic analysis is ongoing to clarify these relationships. Discussion/Significance of Impact: This study highlights how participation in programs like CLR Academy may improve ethnic and racial minority youth diabetes risk factors. Staff and participant insights on mechanisms driving these health improvements may offer strategies that can be applied to similar programs focused on reducing marginalized youth’s diabetes risk.